476 The Role of Medical Students in an International, Collaborative, Multi-Centre Global Surgery Study. (12th October 2021) - Gandhi, S; Raj, R; Dominic, C; Taylor, E H; Politis, M; Hussain, S. Namayah F; Bandyopadhyay, S; Peter, N; Lakhoo, K
Abstract: Introduction: The gaps in formal education caused by the pandemic have provided medical students with opportunities to redefine their role in settings across clinical medicine, education and research. This task shifting could provide avenues for students to engage with global surgery, where the cultivation of research skills, networking, and global collaboration amongst students is imperative for sustainable progress. COVIDPaedsCancer is an international collaborative cohort study assessing the impact of the pandemic on paediatric cancer services. We aimed to trial a student and junior doctor-lead team to perform the day-to-day running of this research. Method: An operations team of 47 students and junior doctors across 11 countries was assembled. Sub-teams were created for social media, network management, email communications, REDCap, research support and graphics. Together, they ran the study under guidance from the steering committee. Results: To date, the operations team has coordinated study collaborators in collecting data for 1252 patients from 78 centres across 39 countries. Cooperation between sub-teams enabled the recruitment of collaborators from 558 hospitals in total. They also identified 2 errors in the protocol and resolved them with steering committee input, and continuously managed hospital leadership issues and general queries throughout the course of the study. The team was able to adapt in response to the evolving needs of collaborators and the steering committee. Conclusions: Medical students were able to aid the delivery of an international, multicentre, collaborative, global surgery research study while benefiting from learning opportunities, networking opportunities, and developing interest and understanding of global surgery.